Etiological Beliefs about Illness in Panic Disorder: Relationship with Baseline Demographic and Clinical Characteristics and Impact on Treatment Response - El Amiri, Sawsane (Université d'Ottawa / University of Ottawa, 2017)
Purpose: The relation between the causal attributions of individuals with panic disorder (PD) and their health outcomes remains relatively unexplored. Therefore we examined 1) the relationship between participants’ etiological beliefs about PD and baseline demographic and clinical characteristics and 2) whether participants’ etiological beliefs about PD predicted compliance, clinical response, and side effect profiles with the treatments they were assigned. Method: The study included 251 participants. A series of multiple linear regressions were used to evaluate the relationship between participants’ causal attributions, measured by the Etiological Model Questionnaire, and their baseline characteristics. To determine whether these beliefs predicted treatment outcome, logistic and linear regressions were conducted. Results: Our results revealed that participants with a family history of psychiatric illnesses were more likely to endorse biological etiological beliefs whereas those with a younger age, comorbid psychiatric disorders, and a history of suicide attempts were more likely to attribute their illness to psychological causes. Participants experiencing impairment in family life endorsed both psychological and environmental causal beliefs, while those reporting higher fear of body sensations and agoraphobic cognitions were more likely to attribute their illness to biological and psychological causes. With regards to treatment outcome, results indicated that participants who endorsed psychological and environmental etiological beliefs experienced more severe symptoms 12 weeks following treatment; irrespective of the type of treatment they received. Implications: The consideration of individuals’ causal attributions might help health-care professionals better assist clients by communicating a more balanced perspective of the causes of PD and deliver interventions that are in line with clients’ individual beliefs.
Keywords: Etiological beliefs; Panic disorder; Self-administered CBT; Sertraline; Clinical characteristics; Treatment outcome